Domination of Regional Wealth as a Determining Factor of Financial Statement Disclosure - Johan Arifin (Jurnal Akuntansi dan Keuangan, 2020)
AbstractUsing Stewardship theory, this study examines the factors that influence the level of mandatory disclosure within financial statements of provincial governments in Indonesia, including size of government, regional wealth, number of Regional Working Units (SKPD), administrative age of government and audit findings. By applying the purposive sampling method, this study uses a sample of financial statements from 27 provinces in Indonesia during 2016 to 2018, therefore the total sample is 81 financial statements. The findings reveal that there is a moderate level of compliance with key mandatory disclosures (61,33%). In addition, the regression analysis shows that from the five potential predictor variables, regional wealth is the only predictor that is significantly positive towards the level of mandatory disclosure within financial statements of Indonesian provincial governments. Given overall non-compliance rate of over 38% there is a clear need for the Indonesian government especially the Supreme Audit Board (BPK) to better enforce provincial government's compliance combined with important financial reforms and regulations.